Pattern of Psychiatric Admissions in Private Psychiatric Hospitals in Chattogram (IAHS Medical Journal, 2023)
Background: Globally, psychiatric disorders have become an alarming issue. Nowadays, it is highly recognized among the population of Bangladesh. Around 970 million people suffer from various psychiatric disorders and depression is the 4th leading cause of disability worldwide. They immensely contribute to the global burden of diseases. This study determines admission patterns among patients with psychiatric disorders in private psychiatric hospitals in Chattogram.Materials and methods: Between July 2021 and June 2022, a cross-sectional study was conducted at Mononibash (A Specialized Psychiatric Hospital) and Chattogram Manoshik Hospital. Purpose sampling method was used and a total of 150 participants included those aged between 13 to 83 years. A semistructured questionnaire was imposed to obtain socio-demographic and other relevant clinical information from patients and attendants. The diagnosis was based on clinical interviews using the Standardized Diagnostic Statistical Method (DSM-V).Results: Among 150 patients 94 (62.67%) were male and 56 (37.33%) were female. In the age group of 21 to 40 years (60%), psychiatric disorders were highly prevalent. The most common psychiatric disorders were Schizophrenia (53.33%), Bipolar affective disorder (24.67%), Brief psychotic disorder (10%), Major depressive disorder (4%), Personality disorder (3.33%), Conduct disorder (1.33%) and other related disorders (2%).Conclusion: These results can help to improve diagnosis, treatment services, prevention of psychiatric disorders, and mental health promotion. Well-designed epidemiological and clinical research is needed to improve and ensure comprehensive healthcare delivery for psychiatric patients.IAHS Medical Journal Vol 5(2), Dec 2022; 38-41